Two-component signaling systems. - Simon, Melvin I.; Crane, Brian R.; Crane, Alexandrine (Methods in enzymology, 2007)
Biochemists and researchers in related life science fields. Key Features: * Presents detailed protocols * Includes troubleshooting tips.